Natural products as part of triple negative breast cancer - Yozlem Kobakova; Maria Moneva-Sakelarieva; Spiro Konstantinov; Georgi Momekov; Stefka Achkova Ivanova; Ventseslava Atanasova; Maria Chaneva; Radoslav Tododrov; Nikolay Bashev; Petar Atanasov (Pharmacia)
Triple negative breast cancer (TNBC) continues to be the breast cancer subtype with the highest recurrence and mortality rates. Treatment of TNBC can be challenging because the disease has different molecular subtypes. Various treatment options are available, such as chemotherapy, immunotherapy, radiation therapy, and surgery. Chemotherapy is the most common of these options. The serious side effects of chemotherapy significantly limit its use. Long-term toxicity can affect the majority of breast cancer survivors, significantly reducing their quality of life. Immunotherapy causes a wide variety of toxic effects called immune-related adverse events (IRAEs). This necessitates the search for alternative methods of treatment for triple negative breast cancer. More and more research in this field is focused on single or combination therapy based on compounds obtained from natural sources. Natural products such as curcumin, resveratrol, and epigallocatechin-3-gallate, with their mechanisms of action and antineoplastic properties, are the subject of numerous studies.